Self-reinforcing market dominance - Daniel Halbheer; Ernst Fehr; Lorenz Goette; Armin Schmutzler (University of Zurich, Socioeconomic Institute, 2007)
Are initial competitive advantages self-reinforcing, so that markets exhibit an endogenous tendency to be dominated by only a few firms? Although this question is of great economic importance, no systematic empirical study has yet addressed it. Therefore, we examine experimentally whether firms with an initial cost advantage are more likely to invest in marginal cost reductions than firms with higher initial costs. We find that the initial competitive advantages are indeed self-reinforcing, but subjects in the role of firms overinvest relative to the Nash equilibrium. However, the pattern of overinvestment even strengthens the tendency towards self-reinforcing cost advantages relative to the theoretical prediction. Further, as predicted by the Nash equilibrium, mean-preserving spreads of the initial cost distribution have no effects on aggregate investments. Finally, investment spillovers reduce investment, and investment is higher than the joint-profit maximizing benchmark for the case without spillovers and lower for the case with spillovers.
Keywords: C90; D43; L13; O31; 330; Cost-reducing Investment; Asymmetric Oligopoly; Increasing Dominance; Experimental Study; Marktführer; Test; Grenzkosten; Investitionsentscheidung; Nash-Gleichgewicht; Theorie